Human Papillomavirus Genotype Association With Survival in Head and Neck Squamous Cell Carcinoma - Scott V. Bratman; Jeffrey P. Bruce; Brian O’Sullivan; Trevor J. Pugh; Wei Xu; Kenneth W. Yip; Fei‐Fei Liu (2016)
trial tweets, 78.6% (144 of 183) concerned immunotherapy and 86.3% (158 of 183) had embedded links directing users to news articles.Only 1 tweet linked to a patient recruitment website (Table 2).Discussion | Our investigation shows that the use of Twitter for support (28%) and prevention (28%) dialogues is common.Although some tweets are about clinical trials (18%), virtually none are used for recruitment or provide links to enrollment websites.Social media is a rich and promising avenue for exploring how patients conceptualize and communicate about their specific health issues, but its potential to promote cancer clinical trial accrual remains unknown. 5 This is a pilot study with a relatively small sample size, and findings are therefore exploratory.Enrollment into clinical trials is often the best treatment option for patients, but only 2% to 7% of adult cancer patients participate in clinical trials. 2 Social media may provide an infrastructure that allows investigators to interact with the public in new ways, including stimulating interest in new clinical trials with targeted messages to connect patients, caregivers, and families with potential trial enrollment websites.Social media could become a very useful tool for clinical researchers but may also pose some challenges with respect to both noncoercive content and the assurance of privacy, both of which the IRBs will need to consider carefully.Future efforts are needed to explore whether Twitter can emerge as a viable medium for promoting accrual to clinical trials.